1996
DOI: 10.1046/j.1365-201x.1996.470184000.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuronally mediated anion secretion induced by short‐chain fatty acids in the rat distal small intestine

Abstract: The short-chain fatty acids acetate, propionate and butyrate induced a concentration-dependent increase of short-circuit current (Isc) in the rat distal small intestine in vitro. They were ineffective in the proximal small intestine. The increase of lsc in the distal small intestine was dependent on the presence of Cl- and HCO3- ions. It was blocked by the inhibitor of the Na(+)-K(+)-Cl(-) -cotransporter, bumetanide, and by the Cl- channel blocker, 5-nitro-2-(3-phenylpropylamino)-benzoate, indicating that shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Luminal SCFAs are not only absorbed as nutrients across the intestinal epithelium, but also influence various physiological and pathophysiological functions of the gastrointestinal (GI) tract (Cummings et al 1995;Topping and Clifton 2001;Andoh et al 2003;Kles and Chang 2006). For example, SCFAs stimulate colonic blood flow (Mortensen and Hielsen 1995), fluid/electrolyte uptake (Binder and Mehta 1989;Lutz and Scharrer 1991;Vidyasagar and Ramakrishna 2002), smooth muscle contraction (Yajima 1985;Mitsui et al 2005a, b), transepithelial chloride secretion (Yajima 1988;Hubel and Russ 1993;Diener et al 1996), exert proliferative stimuli of colonic epithelial cells (Sakata 1987;Kripke et al 1989;Scheppach et al 1992), and prevent colorectal cancer (D'Argenio et al 1996). It is also known that the dietary fiber and SCFAs are possible to have efficacy for the inflammatory bowel disease (IBD), e.g.…”
Section: Introductionmentioning
confidence: 96%
“…Luminal SCFAs are not only absorbed as nutrients across the intestinal epithelium, but also influence various physiological and pathophysiological functions of the gastrointestinal (GI) tract (Cummings et al 1995;Topping and Clifton 2001;Andoh et al 2003;Kles and Chang 2006). For example, SCFAs stimulate colonic blood flow (Mortensen and Hielsen 1995), fluid/electrolyte uptake (Binder and Mehta 1989;Lutz and Scharrer 1991;Vidyasagar and Ramakrishna 2002), smooth muscle contraction (Yajima 1985;Mitsui et al 2005a, b), transepithelial chloride secretion (Yajima 1988;Hubel and Russ 1993;Diener et al 1996), exert proliferative stimuli of colonic epithelial cells (Sakata 1987;Kripke et al 1989;Scheppach et al 1992), and prevent colorectal cancer (D'Argenio et al 1996). It is also known that the dietary fiber and SCFAs are possible to have efficacy for the inflammatory bowel disease (IBD), e.g.…”
Section: Introductionmentioning
confidence: 96%
“…Following Yajima's report, Hubel and Russ [8] showed the same response of propionate in the rat distal colon and additionally reported the negative effects of TTX (10 −7 M); a neural (N-type) calcium (Ca 2+ ) channel blocker, ω-conotoxin (10 −7 M); a non-selective cyclooxygenase (COX) inhibitor, piroxicam (10 −5 M); a lipoxygenase inhibitor, nordihydroguaiaretic acid (10 −5 M); a 5-hydroxytryptamine (5-HT)-3 (5-HT 3 ) receptor antagonist, metoclopramide (10 −5 M); a 5-HT 2 receptor antagonist, xylamidine (10 −5 M); and, tachyphylaxis to capsaicin, calcitonin gene-related peptide (CGRP), substance P, histamine, prostaglandin (PG) E 2 , and 5-HT [8]. In the rat distal colon, but not the proximal colon, and small intestine, it has been reported that acetate as well as propionate and butyrate induce TTX-and atropine-sensitive anion secretion [9]. However, there is no follow-up for the SCFA-induced reflex secretory response; thus, its mechanism still remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…low concentrations (< 100 ìÒ) increased and high concentrations decreased motility (Yajima, 1985;Squires et al 1992). It has been shown that enteric neurones are involved in the response of the gut to SCFAs (Yajima, 1985;Diener et al 1996). AH neurones occur in different regions of the gut, namely in the antrum (Tack & Wood, 1992), the duodenum and ileum (Nishi & North, 1973;Hirst et al 1974), in the proximal colon (Messenger et al 1994), the distal colon (Wade & Wood, 1988) and the rectum of the guinea-pig (Tamura & Wood, 1989).…”
mentioning
confidence: 99%